Patient reported adverse events among epileptic patients taking antiepileptic drugs. (3rd May 2018) - Ayalew, Mohammed Biset; Muche, Esileman Abdela
Objective: The aim of this study was to assess patient reported adverse events and associated factors among epileptic patients taking antiepileptic drugs on follow-up at University of Gondar Referral Hospital. Methods: Cross-sectional study was done on 354 adult epileptic patients. Patients who were on antiepileptic drugs for epilepsy treatment for less than a year, those who were below 18 years old, patients with incomplete information on the chart and those who were involuntary or uncooperative were excluded from the study. Data were entered in to SPSS version 20.0 for analysis. Bivariate and multivariate binary logistic regression analysis was done to see factors associated with antiepileptic drugs adverse effect. Level of statistical significance was declared at p ≤ 0.05. Result: Generalized tonic clonic seizure was the most common (86.2%) type of epilepsy. A total of 79 adverse events were reported. The most frequently encountered adverse events were fatigue (5.08%), gastrointestinal disturbance (4.24%) and sedation/depression (4.24%). Adverse drug effect of antiepileptic drugs was significantly associated with illiterate educational status, increased number of antiepileptic drugs, no seizure during last follow-up and last year, and 1–5 seizures for the last year. Conclusion: About one-sixth of epileptic patients reported adverse drug effects. Adverse drug effects were more commonly seen in patients with low educational status, increased number of antiepileptic drugs, absence of seizure during last follow-up and last year, and 1–5 seizures for the last year. So clinicians should give emphasis for patients with these characteristics to counsel on how to minimize or prevent adverse drug events from antiepileptic drugs or giving reassurance about it if it is minor.